2022
DOI: 10.2463/mrms.rev.2021-0050
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Future Directions in Brain MR Imaging Studies in Schizophrenia: Toward Elucidating Brain Pathology and Developing Clinical Tools

Abstract: Schizophrenia is a common severe psychiatric disorder that affects approximately 1% of general population through the life course. Historically, in Kraepelin's time, schizophrenia was a disease unit conceptualized as dementia praecox; however, since then, the disease concept has changed. Recent MRI studies had shown that the neuropathology of the brain in this disorder was characterized by mild progression before and after the onset of the disease, and that the brain alterations were relatively smaller than as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 150 publications
(230 reference statements)
1
7
0
Order By: Relevance
“…In line with previous studies of volumetric alterations in the schizophrenia spectrum, 1–6 , 13 we found that a pattern of morphological features, including the IFG pars triangularis, putamen, and pallidum contributed to the identification of ChSZ patients. Using a manual tracing method within the IFG, we previously found that the volume reduction in the IFG pars triangularis is a disease-specific feature in the schizophrenia spectrum, such as UHR, 21 FEP, 21 and ChSZ, 23 and the extent of structural alteration was associated with brain activity during a verbal fluency test in FEP.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies of volumetric alterations in the schizophrenia spectrum, 1–6 , 13 we found that a pattern of morphological features, including the IFG pars triangularis, putamen, and pallidum contributed to the identification of ChSZ patients. Using a manual tracing method within the IFG, we previously found that the volume reduction in the IFG pars triangularis is a disease-specific feature in the schizophrenia spectrum, such as UHR, 21 FEP, 21 and ChSZ, 23 and the extent of structural alteration was associated with brain activity during a verbal fluency test in FEP.…”
Section: Discussionsupporting
confidence: 92%
“…This limitation needs to be considered when demographic variables are known to affect biological markers, such as brain measurements. In this case, large samples with a wide age range (e.g., more than 1,000 HCs from those aged 15-60 years) are needed to determine the deviation from normative healthy development and aging (18) , (29) , (30) , (31) . These complications do not discourage the use of the cross-disorder study approach, but instead, they emphasize the need for better qualitative controls capable of considering both clinical disorder progression and additional confounding demographics.…”
Section: Current Progress In Human Brain Mri Studies For Psychiatric ...mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has been used as a candidate research tool in elucidating the pathological characteristics of these disorders and applying the biological markers to clinical settings in the future (18) . In this review, we intend to introduce a selection of recent and relevant MRI studies to highlight the current progress and limitations of MRI research in psychiatry.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous studies reported altered subcortical volumes in various psychiatric disorders, including MDD and schizophrenia (7)(8)(9)(10)(11)(12). Subcortical regions, including the caudate [7,8], thalamus, and hippocampus [8], are found to be smaller in MDD patients compared to healthy controls (HCs); however, the study conducted using MRI of 8,590 samples from the UK Biobank did not observe any statistically signi cant differences between individuals with depressive symptoms and HCs in any of the subcortical volumes [9].…”
Section: Introductionmentioning
confidence: 99%
“…Subcortical regions, including the caudate [7,8], thalamus, and hippocampus [8], are found to be smaller in MDD patients compared to healthy controls (HCs); however, the study conducted using MRI of 8,590 samples from the UK Biobank did not observe any statistically signi cant differences between individuals with depressive symptoms and HCs in any of the subcortical volumes [9]. In contrast, in schizophrenia several consistent changes in subcortical volume have been reported [10,11]. The Enhancing Neuroimaging Genetics through Mega-Analysis (ENIGMA) Consortium Schizophrenia Working Group conducted a multicenter meta-analysis and found that patients with schizophrenia had smaller volumes in the hippocampus, amygdala, thalamus, and accumbens and larger volumes in the pallidum compared to HCs [12].…”
Section: Introductionmentioning
confidence: 99%